A Case of Multidrug-Resistant Lance-Adams Syndrome Successfully Treated With Phenobarbital. Issue 1 (9th November 2022) - Yeniay Süt, Nurşah; Yıldırım, Miraç; Bektaş, Ömer; Kendirli, Tanıl; Teber, Serap
Abstract : Objective: Lance-Adams syndrome is a rare but devastating disorder characterized by rest, action, and stimulus-sensitive myoclonus after cardiorespiratory arrest. We aimed to present a case of multidrug-resistant Lance-Adams syndrome that was successfully treated with oral phenobarbital therapy. Method and Results: We report a previously healthy 11-year, 6-month-old boy was referred to our pediatric intensive care unit because of severe hypoxic ischemic brain injury due to sudden cardiorespiratory arrest. On the 15th day of hospitalization, he developed myoclonic jerks involving his limbs, trunk, and eyes. Despite many antiseizure medications in different combinations, myoclonic jerks persisted. Then, phenobarbital was started, and myoclonic jerks disappeared the next day. At the final evaluation, additional phenobarbital treatment was continued for 6 months and the patient remained myoclonus-free during this time. Conclusions: To the best of our knowledge, this case is the first report describing significant improvement with phenobarbital in a patient with multidrug-resistant Lance-Adams syndrome. We suggest that phenobarbital is an effective option and should be kept in mind in patients with multidrug-resistant Lance-Adams syndrome.